CLEAN AND HEALTHY LIVING BEHAVIOR RELATIONSHIP WITH MOTHER'S ANXIETY IN CHILDREN WITH DIARRHEA AT PUSKESMAS KUNIR - Imroatul Mas'uda (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2022)
Diarrhea is a disease that is commonly found in children less than five years old. Hygiene behavior is very important and must be considered because it affects a person's health. This study aims to analyze the relationship between levels of clean and healthy behavior with maternal anxiety in children with diarrhea. This research was quantitative research with a cross-sectional approach. The population of this study amounted to 18 respondents with the Accidental Sampling sampling technique. Analyzed with SPSS using Spearman rank. The results from 18 respondents were obtained as many as 8 (44.45%) Clean and Healthy Life Behaviors were good, 1 (5.55%) Clean and Healthy Life Behaviors were lacking, and 9 (50%) Clean and Healthy Life Behaviors were bad. While the mother's anxiety level was found to be 7 (38.88%) mild anxiety, 9 (50%) moderate anxiety 2 (11.12%) severe anxiety, an analysis of research results using spearman rank obtained a value = 0.000. The results showed 0.000 <0.05 so it can be concluded that there is a relationship between the level of clean and healthy behavior and maternal anxiety in children with diarrhea.